Determinants of circulating calcitonin value: analysis of thyroid features, demographic data, anthropometric characteristics, comorbidities, medications, and smoking habits in a population with histological full exclusion of medullary thyroid carcinoma - Trimboli, Pierpaolo; Peloni, Giuseppe; Confalonieri, Dorotea; Gamarra, Elena; Piticchio, Tommaso; Frasca, Francesco; Makovac, Petra; Piccardo, Arnoldo; Ruinelli, Lorenzo (Frontiers in Oncology, 2024)
Objective Calcitonin (Ctn) measurement is crucial for the early diagnosis of medullary thyroid carcinoma (MTC). However, Ctn levels can be skewed/elevated due to other reasons, and the Ctn upper reference value remains controversial. In this field, studies have heterogeneous settings, published data are controversial, and no evidence has been achieved. The study’s aim was to evaluate all previously investigated Ctn determinants in a population with histological exclusion of MTC. Methods The institutional records from 2010 to 2022 were reviewed to select patients with thyroid nodules who had undergone total thyroidectomy with histological exclusion of MTC and who had tested for Ctn just before surgery. Thyroid features, demographic and anthropometric data, comorbidities, medications, and lifestyle information were collected. Univariate and multivariate analyses were performed. Results A total of 127 cases were included. The median age for thyroidectomy was 51 years. Median Ctn was 1.04 pg/mL (interquartile range (IQR) 1.04–2.77), with two cases having values above 10 pg/mL. In univariate analysis, Ctn was correlated with gender (p < 0.001), body weight (p = 0.016), height (p = 0.031), body surface area (p = 0.016), thyroid size (p = 0.03), thyroglobulin (p < 0.001), and chronic kidney disease (p < 0.001). After multivariate analysis, the model with the highest accuracy included gender, chronic kidney disease, and thyroid-stimulating hormone (TSH) with an adjusted R-squared of 0.4. Conclusions This study demonstrates, in a population histologically proven as MTC-free, that the Ctn value is mainly influenced by gender, anthropometric/thyroid features, and chronic kidney disease, with the further impact of TSH.